Species of cyathostomin resistant to albendazole in equines, Cuba - Salas-Romero, Josmel (2017)
This study aimed to evaluate the efficacy of anthelmintic used in an equine ranch in Cuba. The faecal egg count reduction test of Strongyles (FECRT) was used to evaluate albendazole and ivermectin. Thirty-three horses were selected (18 treated with albendazole, 15 treated with ivermectin). The egg count reduction for albendazole was 38% for micronized albendazole and 33% for albendazole sulfoxide. Ivermectin effectiveness was 100%. Subsequently, four horses that showed high counts of eggs after the albendazole treatment were treated with ivermectin on day 17 after the initial deworming to collect resistant nematodes in the faeces. These nematodes were morphologically identified. It was possible to identified 493 specimens: Cylicocyclus nassatus, Cyathostomum catinatum, Cylicostephanus longibursatus, Cylicostephanus goldi and Cylicostephanus minutus which represented 78.5, 7.7, 6.5, 3.9 and 3.4% respectively. This has been the first report for Cylicostephanus minutus in equines in Cuba. It is concluded that at least five of species of cyathostomes were resistant to albendazole.